You are on page 1of 11

K.V.

JMO 2014

Solution: Lets put n=1


16+3(1)5-5(1)4-15(1)3+4(1)2+12(1)+3
=1+3-5-15+4+12+3 =3
Which is not a perfect square
On putting n=2
26+3(2)5-5(2)4-15(2)3+4(2)2+12(2)+3
=64+96-80-120+16+24+3
=3
Which is not a perfect square
On putting, n=3
36+3(3)5-5(3)4-15(3)3+4(3)2+12(3)+3
=729+729-405-405+36+36+3
=723
Which is not a perfect square
On putting, n=4
46+3(4)5-5(4)4-15(4)3+4(4)2+12(4)+3
=4096+3072-1280-960+64+48+3
=5043
Which is not a perfect square.
For all value of n the unit digit of expression ends with 3
A number is a perfect square if and only if, the unit digit ends with 0,1,4,5,6 or 9
:. For no integer n, n6+3n5-5n4-15n3+4n2+12n+3 is a perfect square.
ALTERNATE SOLUTION
n^6 + 3n^5 - 5n^4 - 15n^3 + 4n^2 + 12n
= n^5(n+3) - 5n^3(n+3) + 4n(n+3)
= (n^5 - 5n^3 + 4n)(n+3)
= n(n+3)(n^4 - 5n^2 + 4)
= n(n+3)(n^2-4)(n^2-1)
= (n-2)(n-1)n(n+1)(n+2)(n+3)
= Product of 6 consecutive integers
= A multiple of 6!
= Unit digit is 0
Thus,
Unit digit of n^6 + 3n^5 - 5n^4 - 15n^3 + 4n^2 + 12n + 3 is 3.
Now, unit digit of a square can be one of 0,1,4,9,6.
Thus, the given expression can never be a perfect square.

Solution:
We proceed by contradiction. Let the probability of rolling an i be p_i and q_i in the two
dice, with i=1,2,...,6. For the first part of the question we have E= {2,3,4,...,12}. Here are
probabilities of rolling each member of E.
Sum Probability
12 p_6q_6
11 p_5q_6+q_5p_6
10 p_5q_5+p_4q_6+q_4p_6
9 p_3q_6+q_3p_6+p_4q_5+q_4p_5
8 p_4q_4+p_2q_6+q_2p_6+p_3q_5+q_3p_5
7 p_1q_6+q_1p_6+p_2q_5+q_2p_5+p_3q_4+q_3p_4
6 p_3q_3+p_1q_5+q_1p_5+p_2q_4+q_2p_4
5 p_1q_4+q_1p_4+p_2q_3+q_2p_3
4 p_2q_2+p_1q_3+q_1p_3
3 p_1q_2+q_1p_2
2 p_1q_1
Due to the symmetry of the table we must have for some
constants f,g,h,m,n that p_6=fq_6=gq_5=hq_4=hq_3=gq_2=fq_1=mp_5=np_4=np_3=mp_2=
p_1 ... ....(*)
Since the probabilities in the table are "homogeneous", we may assume thep_i,q_i are scaled
by some factor. For convenience assume them to be scaled so that p_6=p_1=1 . Thus we are
not dealing with probabilities anymore but merely with a system of equations. Now note that
thef,g,h,m,n cannot be nonpositive, otherwise we get a nonpositive probability somewhere in
(*). Thusf,g,h,m,n>0 . Now consider the probability of rolling a 12 from the table above,
i.e. p_6q_6=q_6 . Using (*) this becomes1/f . As all the probabilities in the table must be
equal for the proposition to hold, it follows they are all=1/f . Now consider the probability of
rolling a7 , i.e. (after
substituting p_6=p_1=1 ) q_6+q_1+p_2q_5+q_2p_5+p_3q_4+q_3p_4=1/f . Substituting in
the p_i,q_i values from (*), this becomes,2/f+2/mg+2/nh=1/for1/f+2/mg+2/nh=0 . But this
contradicts the fact thatf,g,h,m,n>0 .
Thus, it is not possible for the proposition to hold, i.e. to load the dice such that all members
of E are equally likely.

Solution:

a = sin(x) + sin(y) = 2sin((x+y)/2)cos((x-y)/2) - (1)


b = cos(x) + cos(y) = 2cos((x+y)/2)cos((x-y)/2) - (2)

Also, a^2 + b^2 = 2(1 + sin(x)sin(y) + cos(x)cos(y))


= 2(1 + cos(x-y)) = 2(1 + 2cos^2((x-y)/2) -1)
= 4 cos^2((x-y)/2) - (3)

Now:

(a^2 + b^2 + 2b)t^2 - 4at + (a^2 + b^2 - 2b) = 0

Let roots of above equation be and . Then:

+ = 4a/(a^2 + b^2 + 2b)


= (8sin((x+y)/2)cos((x-y)/2))/(4 cos^2((x-y)/2) + 4cos((x+y)/2)cos((x-y)/2))
= (2 sin((x+y)/2))/(cos((x-y)/2) + cos((x+y)/2))
= 2(sin(x/2)cos(y/2) + sin(y/2)cos(x/2))/(2cos(x/2)cos(y/2))
= tan(x/2) + tan(y/2) - (4)

Also:

= (a^2+b^2-2b)/(a^2+b^2+2b)
= (4 cos^2((x-y)/2) - 4cos((x+y)/2)cos((x-y)/2))/(4 cos^2((x-y)/2) + 4cos((x+y)/2)cos((x-y)/2))
= (cos((x-y)/2) - cos((x+y)/2))/(cos((x-y)/2) + cos((x+y)/2))
= (2sin(x/2)sin(y/2))/(2cos(x/2)cos(y/2))
= tan(x/2)tan(y/2) - (5)
From (4) and (5)
Thus, and are tan(x/2) and tan(y/2).
Thus, these are the required solutions of the given equation.

Solution: Let triangle ABC as below:

B C
a

Let angle B= BC=a


Then angle A=2 AC=b

So, angle C=180-3 AB=c


Applying sin rule

a=k sin 2
b= k sin
c= k sin (180-3 )=k sin
To prove:
a2=b(b+c)
RHS =k sin (k sin + k sin 3 )
= k2 sin2 +k2sin sin3 )
=k2(sin2 +sin (3sin -4sin3 ))
=k2(4sin2 -4sin4 )
=4 k2sin2 (1-sin2 )=4k2sin2 cos2
=k2sin22
= a2
Hence proved.
Q.No. 5

Q.No. 6

Solution:

Let each side of the polygon be of length a,


since

A1A2=A2A3=a,

Therefore from A1A2A3,


A1A3=2a cos(
/n),

Also from A A2A3A4,

A2A4=2a cos( /n),

Since the polygon A1A2.An is regular, its vertices lie on a circle. In particular, the
quadrilateral A1A2A3A4 is cyclic

By Ptolemys theorem,

A1,A2.A3A4+ A1A4 .A2A3=A1A3.A2A4

a2 +A1A4.A2A3=[2a cos ( /n)] 2

i,e. A1A4=a(4 cos2 /n -1).

Since = +

Therefore,

= +

2cos(

8cos^3 (

x=cos

8x3-4x2-4x+1=0 ---------------(i)

We shall show that the root of (i) are cos cos 3

Let 7 .

cos 4 =cos[(2n+1) -3

2(2cos -1)2-1=-(4cos3 -3cos

8cos4 +4cos3 -8cos2 -3cos +1=0

(cos +1)[8cos^3

Now(ii) is satisfied by

Rejecting the factor cos +1 which corresponds to

cos
Cos 3

are the roots of

8y3-4y2-4y +1=0 ---------------------(iii)

Since equations(i) and (iii) are the same, therefore the roots of (i) are cos

Therefore we must have n=7.

Q.No. 7 Solution:

On rationalizing, the expression =


X

+ -

- + -

3-b

Now for, numerator to be rational

must be rational

must be rational

must be rational

.e. - =0

ab=6 -----------(1)

3a - must be rational,

and must be rational,

Say, a = 3k2, b =2m2

from (1)
3k2.2m2=6
km =1
So, now we have
km=1

k=

So, a = 3k2
= 3/ m2

& b = 2m2

This given expression is a rational number for m , i.e.,

The expression =

+m

m +

+m

For all rational values of

m and m 0,

i.e,

a= and b =2m2

is a rational number.
Question No.

Solution: p(x)=x4 -18x3 +kx2+174x-2015=0.


Let the four roots be v,x,y,z.
According to question
vx=(-31).
here a=1, b=-18, c=k and d=174.
e= -2015.
Product of all roots=c/a.
vxyz=-2015/1.
yz(-31) =-2015.
yz=+2015/+31
yz=65
sum of product of roots taken 3 at a time =-d/a.
xyz +vxy+vyz+xvz = - 174/1
65x+(-31)y +65v+(-31)z=-174.
65(x+v)-31 (y+z) = -174. (i)
Sum of roots = -b/a.
x+v+y+z = -(-18)
x+v =18-y-z.
Putting value of x+v in eq. (1)
65 (18-y-z)-31(y+z)=-174.
1170-65y-65z-31y-31z=-174.
-65(y+z)-31(y+z)=174-1170
(y+z)(-96) =1344
y+z =14.
x+y =18-(y+z).
x+y =18-14
=4
Sum of product of roots taken 2 at a time =c/a.
xy +yz +xv+xz+zv+vy =k/a
-31 +65 +x (y+z) +v (y+z) = k
34+(y+z) (x+v)=k
34 +(14) (4) =k
34+56 =k
So, k=90
The value of k is 90